PEMODELAN SISTEM DINAMIS PENGELOLAAN SAMPAH PESERTA KELAS BELAJAR ZERO WASTE MELALUI PRINSIP 3AH (CEGAH, PILAH, DAN OLAH): indonesia - Hidayah, Nurul (Teknik Lingkungan Universitas Islam Indonesia, 2025)
The waste management problem in Indonesia continues to escalate alongside population growth and urbanization, with waste generation reaching 68 million tons annually, including 15% plastic waste that is difficult to decompose. This study aims to analyze community-based waste management through a system dynamics modeling approach applied to participants of the Zero Waste Learning Class (BZW), which adopts the 3AH principles (Prevent, Sort, Process). Using Causal Loop Diagram (CLD) and Stock and Flow Diagram (SFD), this study maps the interactions between variables such as the number of participants, environmental literacy, waste generation, and the effectiveness of prevention, sorting, and processing activities. Data was collected through surveys of 492 BZW alumni and secondary data on waste management. Simulations were performed using Powersim Studio 10 software, with model validation conducted using the Absolute Mean Error (AME) method, yielding an error rate of 2%, indicating a valid model. This study examines four policy scenarios: Business as Usual (BAU), improved environmental literacy, enhanced waste prevention, and optimized waste processing. The simulation results show that the optimal scenario is increasing the capacity for organic and inorganic waste processing, which successfully reduced residual waste to -56.87 tons by 2030. Furthermore, the amount of sorted waste reached 100% of the generated waste. This study concludes that the system dynamics modeling approach is effective in supporting strategic decision-making for community-based waste management and provides recommendations to enhance environmental literacy and waste processing efficiency to achieve sustainability.